2017
DOI: 10.1016/j.ijscr.2017.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Trauma to an inguinal hernia resulting in bowel rupture: A case report and literature review

Abstract: Graphical abstractThis figure shows the histological section of the perforated ileal segment. H & E, x100, which indicates the chronic inflammation of the mucosa with erosion, bleeding and infiltration of lymphocytes and neutrophils,this together with the patient history of suffering just a minimal injury to the hernia makes us speculate, that the pathological changes of the intestine in the hernia sac tending to be broken may be one of the crucial factors causing this rare,acute and serious situation. This fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Por tal motivo varios autores sugieren la herniorrafía tardía; si bien, sigue siendo un tema de discusión el empleo de mallas en cirugías contaminadas. 2,9,[16][17][18][19][20]…”
Section: Discussionunclassified
“…Por tal motivo varios autores sugieren la herniorrafía tardía; si bien, sigue siendo un tema de discusión el empleo de mallas en cirugías contaminadas. 2,9,[16][17][18][19][20]…”
Section: Discussionunclassified
“…An intestinal resection and anastomosis was performed and recovery was uneventful. The hernia was repaired at a later operation due to peritonitis [ 6 ]. A study done by Vyas et al reported that bowel perforation after blunt trauma was more likely to occur in patients over 40 years of age with a pre-existing hernia in comparison with healthy subjects of the same age [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two theories exist to explain the underlying mechanism of perforation in these cases. One argues an increase in the intra-abdominal pressure and transfer of that pressure to the small bowel in a compressed space results in perforation [ 4 , 6 ]. The other theory argues shearing forces, when applied to abdominal hernias, particularly incarcerated hernias, result in direct injury to the hernia sac contents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the absence of bruising or tenderness over the hernia, and the CT showing no evidence of perforation, the injury was likely an immediate blow-out type perforation due to the sudden increase in intra-luminal pressure caused by direct application of force over the herniated bowel. 4 This case highlights the difficulty of timely diagnosis and the need for serial examinations.…”
mentioning
confidence: 93%